Nucleotide dependent functioning of bacterial enhancer binding proteins, activators of sigma54 RNA polymerase - Buck, Martin (Henry Stewart Talks, 2007)
Understanding the origins of nucleotide driven conformational change, Molecular motors powered by ATP, ATPases belonging to the AAA protein family, PspF from E.coli, Phage shock genes, ATP transition state analogue ADPAlF, X-ray crystallographic structural analysis, Initiation of conformational changes, Role of structural changes in sigma54 subunit, Formation of open promoter complexes, Changes in DNA binding properties of sigma54, Structural organisation of the RNAP holoenzyme
Updated at 2016/12/29